Heterologous expression of the isopimaric acid pathway in Nicotiana benthamiana and the effect of N-terminal modifications of the involved cytochrome P450 enzyme. Issue 1 (December 2015) - Gnanasekaran, Thiyagarajan; Vavitsas, Konstantinos; Andersen-Ranberg, Johan; Nielsen, Agnieszka; Olsen, Carl; Hamberger, Björn; Jensen, Poul
Abstract Background Plant terpenoids are known for their diversity, stereochemical complexity, and their commercial interest as pharmaceuticals, food additives, and cosmetics. Developing biotechnology approaches for the production of these compounds in heterologous hosts can increase their market availability, reduce their cost, and provide sustainable production platforms. In this context, we aimed at producing the antimicrobial diterpenoid isopimaric acid from Sitka spruce. Isopimaric acid is synthesized using geranylgeranyl diphosphate as a precursor molecule that is cyclized by a diterpene synthase in the chloroplast and subsequently oxidized by a cytochrome P450, CYP720B4. Results We transiently expressed the isopimaric acid pathway inNicotiana benthamiana leaves and enhanced its productivity by the expression of two rate-limiting steps in the pathway (providing the general precursor of diterpenes). This co-expression resulted in 3-fold increase in the accumulation of both isopimaradiene and isopimaric acid detected using GC-MS and LC-MS methodology. We also showed that modifying or deleting the transmembrane helix of CYP720B4 does not alter the enzyme activity and led to successful accumulation of isopimaric acid in the infiltrated leaves. Furthermore, we demonstrated that a modified membrane anchor is a prerequisite for a functional CYP720B4 enzyme when the chloroplast targeting peptide is added. We report the accumulation of 45–55 μg/g plant dry weight of isopimaric acid four days after the infiltration with the modified enzymes. Conclusions It is possible to localize a diterpenoid pathway from spruce fully within the chloroplast ofN. benthamiana and a few modifications of the N-terminal sequences of the CYP720B4 can facilitate the expression of plant P450s in the plastids. The coupling of terpene biosynthesis closer to photosynthesis paves the way for light-driven biosynthesis of valuable terpenoids.